2015
DOI: 10.1177/0333102415596442
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of primary headache disorders diagnosed according to ICHD-3 beta in three different social groups

Abstract: Headache prevalence was high and differed markedly among the three social groups. It is important that headache epidemiology also focus on socially defined groups in order to target future preventive efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
1
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 45 publications
5
22
1
9
Order By: Relevance
“…Our results are in agreement with those of the study conducted by Lebedeva et al [40] that reported the highest prevalence of migraine and TTH among students. Similarly, we reported a high prevalence of migraine among medial students in Kuwait [14].…”
Section: Discussionsupporting
confidence: 94%
“…Our results are in agreement with those of the study conducted by Lebedeva et al [40] that reported the highest prevalence of migraine and TTH among students. Similarly, we reported a high prevalence of migraine among medial students in Kuwait [14].…”
Section: Discussionsupporting
confidence: 94%
“…Blood donors were chosen as a mixed group who had much similarity with general population. In our previous study of the same population as in the present study, we found that blood donors had a prevalence of migraine and TTH similar to the general population . Social groups are not the same as occupational groups.…”
Section: Methodssupporting
confidence: 69%
“…We previously found that the prevalence of migraine and TTH varied considerably between social groups, primarily because students had a higher prevalence of both migraine and TTH and workers had a lower prevalence of TTH . Our hypothesis in this study was that factors associated with migraine and TTH differ not only between sexes but also between social groups.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…1 Within the United States, migraine prevalence has remained highest among Native Americans, followed by whites, and they are more prevalent in females than in males, with a 2:1 to 3:1 ratio. 2,3 Migraine sufferers are more likely to experience depression, anxiety, and chronic pain. This leads to increased health care costs and lost work productivity.…”
mentioning
confidence: 99%